2013
DOI: 10.1152/ajpendo.00197.2013
|View full text |Cite
|
Sign up to set email alerts
|

MLK3 promotes metabolic dysfunction induced by saturated fatty acid-enriched diet

Abstract: MLK3) is a mitogenactivated protein kinase kinase kinase (MAP3K) that mediates JNK activation in response to saturated fatty acids in vitro; however, the exact mechanism for diet-induced JNK activation in vivo is not known. Here, we have used MLK3-deficient mice to examine the role of MLK3 in a saturated-fat diet model of obesity. MLK3-KO mice fed a high-fat diet enriched in medium-chain saturated fatty acids for 16 wk had decreased body fat compared with wild-type (WT) mice due to increased energy expenditure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Palmitic acid activated both kinases in PMH but the PERK inhibitor, which effectively inhibited PERK [47, 48], did not inhibit PKR. The mechanism for palmitic acid induced selective PERK activation and the MAPK signaling pathway which leads to JNK activation requires further study, but based on published work is likely to involve MLK3 [49-51]. Interestingly, ER stress in hematopoietic stem cells has recently been reported to selectively activate PERK and predispose to apoptosis [52].…”
Section: Discussionmentioning
confidence: 99%
“…Palmitic acid activated both kinases in PMH but the PERK inhibitor, which effectively inhibited PERK [47, 48], did not inhibit PKR. The mechanism for palmitic acid induced selective PERK activation and the MAPK signaling pathway which leads to JNK activation requires further study, but based on published work is likely to involve MLK3 [49-51]. Interestingly, ER stress in hematopoietic stem cells has recently been reported to selectively activate PERK and predispose to apoptosis [52].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the activation of the c-Jun terminal kinase (JNK) pathway by SFA was demonstrated in in vivo investigations [14], contributing to the development of hepatic steatosis and insulin resistance, as well as activation of pro-inflammatory M1 macrophages. Other in vitro studies showed that palmitate may induce endoplasmatic reticulum (ER) and oxidative stress in hepatocytes [15] and trigger the inflammasome via the activation of macrophages through TLR2/1 dimerization [16].…”
Section: Circulating Lipidsmentioning
confidence: 99%
“…Indeed, obesity is associated with increased JNK activity in human omental adipose tissue (Bashan et al 2007). Obesity-induced JNK activation is mediated, in part, by free fatty acids (FFAs) that activate the mixed-lineage protein kinase pathway (Jaeschke and Davis 2007;Gadang et al 2013;Kant et al 2013). The mechanism of FFA signaling may involve G-proteincoupled receptors (Talukdar et al 2011) or nonreceptor mechanisms (Holzer et al 2011) that cause activation of the tyrosine kinase Src in lipid raft domains of the plasma membrane (Holzer et al 2011).…”
mentioning
confidence: 99%